2015
DOI: 10.1161/atvbaha.114.304389
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Mobilizes Spleen Monocytes to Promote the Development of Abdominal Aortic Aneurysm in Apoe −/− Mice

Abstract: Objective-Abdominal aortic aneurysm (AAA) is widespread among elderly people and results in progressive expansion and rupture of the aorta with high mortality. Macrophages, which are the main population observed within the site of aneurysm, are thought to derive from circulating monocytes although no direct evidence has been provided to date. In this study, we were particularly interested in understanding the trafficking behavior of monocyte subsets in AAA and their role in disease pathogenesis. Approach and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 59 publications
10
99
0
Order By: Relevance
“…Many recent studies have also demonstrated that AngII induces AAAs in normolipidemic mice [5][6][7] . The approach of infusing AngII has been applied to induce AAAs and explore molecular mechanisms as well as development of potential therapeutic strategies (e.g., [5][6][7][8][9][10][11][12][13][14][15] ) since this model recapitulates many features observed in human AAAs. For example, risk factors of human AAAs such as smoking, aging, and male gender also augment AngII-induced AAAs in mice 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have also demonstrated that AngII induces AAAs in normolipidemic mice [5][6][7] . The approach of infusing AngII has been applied to induce AAAs and explore molecular mechanisms as well as development of potential therapeutic strategies (e.g., [5][6][7][8][9][10][11][12][13][14][15] ) since this model recapitulates many features observed in human AAAs. For example, risk factors of human AAAs such as smoking, aging, and male gender also augment AngII-induced AAAs in mice 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Ang II concentration increases with aging in nonhuman primates. 6 Moreover, Ang II mediates the age-dependent cardiomyopathy, 7 mimics age-associated carotid arterial remodeling, 8 promotes abdominal aortic aneurysms, 9,10 and triggers agerelated contractile dysfunction. 11 In addition, inhibition of the Ang II type 1 receptor promotes longevity in mice.…”
mentioning
confidence: 99%
“…The function of the spleen is important because this organ serves as a reservoir of CD11b + Ly6C hi inflammatory monocytes. Interestingly, splenectomy partially protects from Ang II-induced AAA formation, probably through this mechanism (41). Data from Ang II infusion in IL-6-/-and KLF6-/-mice demonstrate that both IL-6 and GM-CSF are necessary for the full manifestation of aortic pathology as these cytokines amplify aortic cytokine production and promote leukocyte recruitment and maturation.…”
Section: Il-6/mcp-1 Amplification In Vascular Inflammationmentioning
confidence: 98%